Large-Scale Agile Frameworks: A Comparative Review - Fernando Almeida; Eduardo Espinheira (Journal of Applied Sciences, Management and Engineering Technology, 2021)
This study aims to identify and systematically compare the main large-scale agile frameworks that companies can adopt to manage the work of large-scale and distributed teams. Through this, companies can more consciously perform a better-informed decision on the choice of the framework that best fits the practices and challenges of their organizations. This work employs a qualitative approach supported by an exploratory analysis that identifies and explores the processes of migration to a large-scale agile. In the first phase, fifteen assessment criteria for scaling agile are discussed. In a second phase, these criteria are used to perform a comparative analysis of six large-scale agile frameworks (i.e., DAD, LeSS, Nexus, SAFe, Scrum at Scale, and Spotify). The findings reveal there isn't a dominant large-scale agile framework in all dimensions. However, it is possible to identify frameworks like Nexus and Spotify that target smaller teams and offer low technical complexity. These frameworks easily accommodate changes, while there are other frameworks like SAFe and DAD that offer high levels of scalability but require more demanding and deep efforts in changing work processes in an organization.